2015
DOI: 10.1080/17565529.2015.1067178
|View full text |Cite
|
Sign up to set email alerts
|

Upland development, climate-related risk and institutional conditions for adaptation in Vietnam

Abstract: In this article, we develop a republican framework for relational animal ethics, recently popularized in Donaldson and Kymlicka's Zoopolis. This republican framework departs from the focus on negative rights that dominate liberal animal rights theories, especially as concerns our relations to wild animals. Our proposed framework appeals to a republican standard of non-arbitrariness, or non-domination, for human interferences with such animals. This legitimation framework is more attentive to relations of care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Almost half of all studies focused on L&D that has already occurred, meaning that there are already on‐the‐ground impacts from climate hazards. Commonly, the empirical L&D studies demonstrated this, such as the nine Global South case studies published in the International Journal of Global Warming (2013) special issue (Bauer, ; Brida, Owiyo, & Sokona, ; Haile, Kusters, & Wagesho, ; Kusters & Wangdi, ; Monnereau & Abraham, ; Opondo, ; Rabbani et al, ; Traore & Owiyo, ; Warner & van der Geest, ; Yaffa, ), among others case studies (e.g., Beckman & Nguyen, ; Gawith, Daigneault, & Brown, ; Lashley & Warner, ; van der Geest & Schindler, ). Studies reported on household and community level residual impacts from both sudden‐ and slow‐onset climate hazards.…”
Section: Resultsmentioning
confidence: 97%
“…Almost half of all studies focused on L&D that has already occurred, meaning that there are already on‐the‐ground impacts from climate hazards. Commonly, the empirical L&D studies demonstrated this, such as the nine Global South case studies published in the International Journal of Global Warming (2013) special issue (Bauer, ; Brida, Owiyo, & Sokona, ; Haile, Kusters, & Wagesho, ; Kusters & Wangdi, ; Monnereau & Abraham, ; Opondo, ; Rabbani et al, ; Traore & Owiyo, ; Warner & van der Geest, ; Yaffa, ), among others case studies (e.g., Beckman & Nguyen, ; Gawith, Daigneault, & Brown, ; Lashley & Warner, ; van der Geest & Schindler, ). Studies reported on household and community level residual impacts from both sudden‐ and slow‐onset climate hazards.…”
Section: Resultsmentioning
confidence: 97%
“…Conversely, financing mechanisms and resources mobilized for adaptation are not necessarily earmarked as such, and it is even highly possible that so-called adaptation finance represents only a portion of the actions that can be considered as adaptation action. In practice, adaptation goals (and practices) are intertwined with other goals and practices (such as infrastructure development, livelihoods improvement, and reducing risk related to climate hazards for instance), and this will blur the translation from adaptation finance to actual adaptation actions [9][10][11]. In the end, monitoring, reporting, and verifying the alignment of adaptation funding with the necessary protection against uncertain future climate trends is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from changing the mean atmospheric composition due to growing greenhouse gases, the NRC report says that landscape variations could have significant local, regional, and global impacts (Paul et al 2010). LUC is already recognized as a major driver of global climate change (Lambin and Meyfroidt 2011;Foley et al 2015;Hendrix 2017;Beckman and Thi Nguyen 2017). A climate analysis in the USA shows that a significant proportion of the increases in temperature in the last few decades have resulted from changes in land use (Kalnay and Cai 2003).…”
Section: Introductionmentioning
confidence: 99%